The associated effects of shift work on absenteeism and productivity among inbound customer service representatives - Co, Damirson A. (2009)
The study involved the associated effects of individual attributes and shift work characteristics in the absenteeism and productivity of a sample size of inbound customer service representatives in one of the biggest call centers in the Philippines. The individual attributes and shift work characteristics were tested alongside one another in the prediction of the outcome measures of: a. Health (probability that an agent will have four or more absences) and b. Productivity (probability that an agent will have a 90% or higher phone time to working hours ratio). 120 call center agents were used as subjects. They were aged between 19 and 42 years old. 49% of them were female and 51% were male. Their job involved handling billing disputes, cable TV programming transactions and pay-per-view request from the subscribers of a cable company in US. This required them to be in shift schedules. Productivity reports and number of absences were extracted from the call center company's database and formed the backbone of statistical analysis. The frequency and severity of pre-identified health risk factors as well as sleeping habits of each agent were inquired from the abbreviated Standard Shiftwork Index Questionnaire which was administered. Stepwise Logistic Regression was used in predicting the absenteeism and productivity outcome. In the final model to predict the probability that an agent will have four or more absences, the result showed that age, shift type, cardiovascular disorder, job satisfaction, and disruption of social and domestic activities were useful predictors. In the prediction of the probability that an agent will be productive, the final regression model indicated that age and shift type were useful predictors. The above findings support the hypotheses that individual attributes shift work and health risk factors affect the absenteeism and productivity of inbound call center agents. Recommendations were presented in order to maximize the unfavorable effects of shift work and its associated health risk factors. The shift interval of three months was suggested to be shortened. The assignment of full time medical expert in the late shifts and the conduct of regular seminar/programs about coping up with the effects of shift work could prove helpful. Holding regular social activities such as family day, sports festival and team building could minimize the disruption of time for social and domestic activities time of the call center agents. The integration of adequate workshop hours on shift work into orientation program could improve the capability of call center agents to handle shift work related issues.